Prevalence of mental health problems and the associated factors among undergraduate students in a public university, Malaysia - Abd Latiff, Latiffah; Aszahari, Muhammad Adzdzin Adlan; Ab Khalek, Nurul Fatihah; Kon, Jian Fang; Ibrahim, Normala (Community Health Society Malaysia, 2014)
Background Majority of mental problems diagnosed in adulthood may have begun earlier during adolescence period. This study aimed to determine the prevalence and associated factors of mental health problems among undergraduate students in a public university in Malaysia. Methods A cross-sectional study among students between the ages of 19 and 25 years old was conducted using stratified sampling from four randomly selected faculties . Respondents were required to answer a self-administered questionnaire consisting of socio-demographic questions, Depression Anxiety Stress Scale-21 (DASS-21), Body Shape Questionnaire-8C (BSQ-8C), Body Mass Index (BMI), Religious Personality, smoking, alcohol consumption and drug use. Results Out of 481 students, 385 completed the questionnaires (80% responce rate). The median age was 20 years, majority of respondents were female (82.9%). Majority (75.1%) were Malay. The prevalence of depression, anxiety and stress symptoms were 27.3%, 60.0% and 22.6% respectively. Factors related to depression included male gender (OR=2.656), Malay ethnicity (OR=3.647), mild (OR=7.297), moderate (OR=3.821) and severe (OR=22.60) concern of body image and religious personality (OR=2.648). There were significant associations between anxiety and mild (OR=3.939), moderate (OR=2.431) and severe (OR=7.785) concern of body image as well as alcohol consumption (OR= 0.316). Furthermore, Malay ethnicity (OR=4.858), lower family monthly income (OR=1.924), mild (OR=3.574) moderate (OR=3.279) and severe (OR=8.632) concern of body image were related to stress. Conclusion The mental health status of undergraduate students are influenced by social and cultural factors that should be the center of attention for inteventions to prevent or reduce mental health problems.